The Effect of Using E-Learning Assisted by Schoology on Physics Learning Outcomes of Students on the Material of Global Warming and Optical Devices - Qalbi, Nafizatul; Sari, Silvi Yulia (Department of Physics Universitas Negeri Padang, 2023)
There is new hope for the problems that often occur in education in Indonesia, namely with the existence of alternative solutions to E - Learning assisted by schoology there are functions that are tailored to the needs, for the learning process. From these problems, researchers concluded that applying varied learning media such as teachers using schoology-assisted e-learning which is online-based. The application of schoology in the learning process can reduce these problems. As students often have difficulty understanding physics material that is abstract. With this schoology is a solution for teachers to communicate well between students to help get a role / part in the discussion and cooperation. Schoology is equipped with many media factors such as video, audio and images that can increase student interest. Schoology helps students to apply technology to learning. This study uses a type of quasi-experimental design, this study aims to directly test the effect of a variable and test the hypothesis of a causal relationship to determine the effect of teaching materials. The sampling technique used in this study is Purposive Sampling, which is based on consideration of the classes taught by the same teacher and classes that have an average daily test score in physics subjects that are almost the same value. For the results of this calculation, the coefficient of determination is 85.32%, which means that student achievement of cognitive abilities is seen from schoology-assisted e-learning teaching materials while 14.68% is due to other things.